Review of Belfast Punk and the Troubles: An Oral History, by Fearghus Roulston - Marie Gemrichová (Review of Irish Studies in Europe, 2023)
Review of Belfast Punk and the Troubles: An Oral History, by Fearghus Roulston (Manchester: Manchester University Press,  2022), 208 pp., ISBN: 978-1-5261-5223-7,  £85.00 (Hardcover)